Enhancing Science Education Through the Student Teams Achievement Division (STAD) Learning Model: An Experimental Study on Process Skills and Learning Outcomes at Middle School - Semi Touwe; Mohammad Amin Lasaiba (STAI Hubbulwathan Duri, 2024)
This study investigates the implementation of the Student Teams Achievement Division (STAD) Learning Model, which emphasizes teamwork and individual accountability. Traditional teaching methods often fail to actively engage students in developing analytical and practical skills. The STAD model aims to enhance students' process skills and learning outcomes in science education. The research was conducted at SMP Muhammadiyah Ambon with seventh-grade students from four classes. Two classes were randomly selected, with class VIIa as the experimental group (30 students) and another class as the control group (30 students). Data were analyzed using descriptive analysis and multivariate analysis (MANOVA) with SPSS version 26.0. A quantitative experimental approach was employed, using a Pre-test, Post-test, and Non-equivalent Control Group design. Data collection focused on science process skills and learning outcomes. The results demonstrated a significant impact of the STAD model on improving learning outcomes and science process skills. There was a notable increase in average scores from pre-test to post-test in both experimental and control groups. MANOVA results (Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root) showed very high F-values, indicating significant differences between the groups in enhancing students' science process skills and learning achievements. The STAD model proved more effective than traditional methods, suggesting its integration into a collaboration-based curriculum. Effective implementation requires STAD-based teacher training, including team formation techniques, motivational strategies, and methods for assessing team performance. Adopting these recommendations can significantly boost student participation, teamwork skills, and overall learning outcomes.